PERLINDUNGAN HUKUM TERHADAP KORBAN PELECEHAN SEKSUAL KEPADA PENYANDANG DISABILITAS DALAM LINGKUNGAN MASYARAKAT - Perwita Chandra Puspa; Oktavia Adi Roesnia; Tsabita Az-zahra; Berliana Clara Bella; Arsya Ghanniyah Hariyadi; Arief Budiono (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Victims of sexual harassment against people with disabilities experience severe consequences. In addition to being vulnerable to prejudice or discrimination, this minority group also has difficulty in accessing adequate legal protection. The purpose of this article is to examine the legal protection provided to people with disabilities who are targets of sexual harassment in society. The research method used is a normative literature review that examines relevant laws, regulations, and practices. According to this study, although there are legal instruments such as Law Number 8 of 2016 concerning Persons with Disabilities and Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (TPKS), there are still a number of obstacles in implementing these laws effectively, such as lack of public awareness, limited access to legal infrastructure, and social stigma against individuals with disabilities. The results of this study highlight the need to improve the capacity of law enforcement, build accessible facilities, and educate the community to create a safe and supportive environment for people with disabilities. This article offers suggestions on tactics to improve legal protection and achieve social justice for victims of sexual disclosure who have disabilities.